2d And 3d Acoustic Metamaterials Using Space Coil Design. Issue 1753 (11th February 2015) - Maurya, Santosh K.; Sahay, Manu; Shukla, Shobha; Saxena, Sumit
ABSTRACT: Various promising applications such as acoustic cloaking, sub-wavelength imaging, acoustic wave manipulation, transmission or reflection control etc. are feasible because of the ability of manipulating sounds and vibrations using artificially engineered "Acoustics meta-materials". Recent works on space-coiling acoustic metamaterials show their extreme constitutive parameters like large refractive index, double negativity and zero mass density. Three dimensional structures have a wide application in sub-wavelength broadband acoustic wave suppression due to huge attenuation. Here we report the study of propagated and transmitted wave through 3D acoustic metamaterials structure using finite element method. Our simulations on 3D structure show a huge absorption/damping over few hundreds kilohertz frequency range.